Effects of dietary Astragalus membranaceus and Codonopsis pilosula extracts on growth performance, antioxidant capacity, immune status, and intestinal health in broilers - Liu, Shun; Xiao, Gengsheng; Wang, Qi; Tian, Jinpeng; Feng, Xin; Zhang, Qingyang; Gong, Li (Frontiers in Veterinary Science, 2023)
The objective of this study was to examine the effects of dietary Chinese herbal medicine (CHM) consisting of Astragalus membranaceus (Fisch.) Bunge (AMT) and Codonopsis pilosula (Franch.) Nannf (CPO) extracts on growth performance, serum biochemical parameters, antioxidant capacity, and intestinal development of broiler chickens. Two groups were formed, each consisting of six replicates of 12 one-day-old healthy male 817 white feather broilers. Broilers were fed either a basal diet (CON group) or a basal diet supplemented with 500 mg/kg CHM. The trial lasted 50 days. CHM supplementation resulted in enhanced feed efficiency and antioxidant capacity in both the serum and liver, while it reduced uric acid and endotoxin levels, as well as diamine oxidase activity (P < 0.05). Additionally, CHM treatment increased the height of jejunum villi and upregulated Claudin-1 expression in the jejunal mucosa accompanied by an increase in the mRNA levels of interleukin-6 (IL-6), interferon-γ (IFN-γ), interferon-β (IFN-β), tumor necrosis factor-α (TNF-α), and anti-inflammatory cytokine interleukin-10 (IL-10) (P < 0.05). The presence of dietary CHM caused an increase in the proportions of Bacteroidetes and unclassified Bacteroidales but led to a decrease in those of Firmicutes and Alistipes (P < 0.05). The composition of the jejunal mucosa microbiota was correlated with the feed conversion ratio, serum metabolites, and gene expression based on Spearman correlation analysis. The findings indicated that the consumption of dietary CHM improved the utilization of feed, increased the mRNA expression of pro-inflammatory cytokines in the jejunal mucosa, and decreased the endotoxin level and activities of diamine oxidase and lactate dehydrogenase in the serum, which could potentially be linked to changes in the gut microbiota of broiler chickens.